FREQUENCY OF PULMONARY HYPERTENSION IN HEMODIALYSIS PATIENTS (The Research of Medical Science Review, 2025)
Background: Pulmonary hypertension (PH) frequently coexists with end-stage renal disease (ESRD) in patients undergoing dialysis. It serves as an independent predictor of heightened morbidity and mortality in these patients. The actual prevalence of PH in our ESRD patients remains uncertain, despite its prognostic importance. Methodology: Study was carried out at Nephrology Department of PIMS Islamabad. 200 patients undergoing chronic maintenance hemodialysis for ESRD and CKD stage 5, specifically patients who have undergone hemodialysis for a minimum of 6 months having age between 18-80 years of both genders were enrolled for the study. Using the echocardiography, pulmonary arterial pressure (PAP) was measured, and those with PAP of 25 mmHg or higher at rest were classified as having pulmonary hypertension. Data was entered and analyzed using SPSS software. Results: The mean age of the participants was 46.84 years ±15.24 SD. PH was observed in 28% (56 out of 200) of the study population. Among these, 58.9% were male suggesting a slightly higher prevalence in males. The analysis of age groups revealed that PH was highest (44.6%) among patients with age 36- 60 years. Stratification was done for various effect modifiers and it was noticed that statistically significant association (p-value ≤ 0.05) was observed for treatment compliance, COPD and hypertension only. Conclusion: Our study found a high prevalence of PH in hemodialysis patients, especially those with hypertension, COPD, and non-compliance with treatment.